Web-based bus vehicle recapitulation information system at type A terminal Kiliran Jao Sijunjung district: Sistem informasi rekapitulasi kendaraan Bus berbasis web pada terminal tipe A Sijunjung - Sevka Azzany, Felia; Putra, Firmansyah; Andang Purnomo, Wulan (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2023)
The kiliran jao bus terminal in sijunjung district is a type A terminal located at the land transportation management center (BPTD) region III province managed by west sumatera.in the field of land transportation. In the procces off data processing at the type A terminal ,kiliran jao still experiences several obtacles in recapping vechiles (between,districs,,cities,provinces) that arrive or will depart. The data collection methods used in the research that has been done therefore a data recapitulation information system is needed that can be done practically and efficiently so that tht data can be neatly arranged and wil make it easier to search again when needed.to solve this problem, the authors decided to design and build a bus vechile recapitulation information system that can facilitate the ministry of transportation officers for the type a terminal kiliran jao based on web,PHP and MySQL.database to facilitate the service of the recapitulation information system or backup data if at anytime needed at the terminal type A kiliran jao sijunjung regency. This system or application can carry out its functions properly based on the results of black box testing showing the application functions are running well on the button functions and others that have been adjusted to the UML design all run properly and according to the desingn.